Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Guru Melalui Motivasi Kerja Sebagai Variabel Intervening (Studi Pada Sekolah Menengah Pertama 23 Kota Malang) - Setyaningsih, Nunik; wati, Ratna; Rokhman, M. Taufiq Noor (Manajemen & Bisnis Jurnal, 2025)
This study aims to determine the effectiveness of work motivation in mediating the influence of organizational culture and organizational commitment on the performance of teachers of SMP Negeri 23 Malang. This study uses a quantitative approach, using the path analysis technique with a sobel test. The research population was 38 teachers with saturated sampling techniques. The results of the study show that organizational culture and organizational commitment have a significant effect on work motivation and performance. Work motivation also has a significant effect on teacher performance. Organizational culture and organizational commitment through work motivation have a positive and significant effect on teacher performance. The implication of this research is that SMP Negeri 23 Malang needs to prioritize strengthening a positive organizational culture to improve work motivation and teacher performance. This requires investment in effective leadership, inclusive rewards programs, and proactive conflict management. By understanding that work motivation acts as a mediator between organizational culture and commitment to teacher performance, schools can design more focused strategies to improve teacher satisfaction and overall student learning outcomes.